Effect of the spatial and seasonal soil heterogeneity over arbuscular mycorrhizal fungal spore abundance in the semi-arid valley of Tehuacán-Cuicatlán, Mexico. - Camargo-Ricalde, Sara Lucía; Esperón-Rodríguez, Manuel (Revista de Biología Tropical, 2005)
Recent studies have shown that some species of Mimosa (Leguminosae-Mimosoideae) create resource islands (RI), rich in soil organic matter and nutrients, as well as in arbuscular mycorrhyzal fungal (AMF) spores, in the semi-arid Valley of Tehuacán- Cuicatlán. The relevance of this fact is that arid and semi-arid regions are characterized by low fertility soils and scarce precipitation, limiting plant species growth and development; this explains why the presence of AM fungi may be advantageous for mycorrhizal desert plants. Fluctuations in AMF spore numbers could be related to environmental, seasonal and soil factors which affect AMF sporulation, in addition to the life history of the host plant. The aim of this study was to asses the impact of spatial (resource islands vs open areas, OA) and seasonal (wet season vs start of dry season vs dry season) soil heterogeneity in the distribution and abundance of AMF spores in four different study sites within the Valley. We registered AMF spores in the 120 soil samples examined. Significant differences in the number of AMF spores were reported in the soil below the canopy of Mimosa species (RI) comparing with OA (RI > OA), and between Mimosa RI themselves when comparing along a soil gradient within the RI (soil near the trunk > soil below the middle of the canopy > soil in the margin of the canopy > OA); however, there were no significant differences between the soil closest to the trunk vs middle, and margin vs OA. Finally, more spores were reported in the soil collected during the wet season than during the dry season (wet > start of dry > dry). Therefore, the distribution of AMF spores is affected by spatial and seasonal soil heterogeneity. This study points out the relevance of Mimosa RI as AMF spore reservoirs and the potential importance of AM fungi for plant species survivorship and establishment in semi-arid regions. AM fungi have recently been recognized as an important factor determining plant species diversity in arid and temperate ecosystems.